Potensi Cuka Kayu Pinus dalam Pengendalian Penyakit Antraknosa pada Cabai Merah - Sri Hartati; Rika Meliansyah; Lindung Tri Puspasari (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2013)
Anthracnose disease caused by Colletotrichum capsici is a major disease on red chili which causes great economic losses. Wood vinegar, as a result of condensation of smoke, can be used as bactericide and fungicide. The use of pine wood vinegar is prospective for controlling anthracnose disease. The objective of this research was to study the potency of pine wood vinegar in controlling anthracnose on red chili. In vitro test was carried out to measure the inhibition of pine wood vinegar against the growth of mycelium mass and the germination of the conidium of C. capsici. The treatments were the concentration of the pine wood vinegar, i.e. 0, 1.5, 2.5, 3.5, 4.5, and 5 %, and a fungicide (2% of antracol) as comparison. The results showed that the lower the concentration of the pine wood vinegar, the lower the inhibition of the mycelium growth. The highest inhibition of the mycelium growth (76.1%) was caused by 5% of the pine wood vinegar, followed by 41.04% inhibition caused by 4.5% concentration. There was no germination of the conidium on all treatments.